Auditoría de gestión y su incidencia en el presupuesto de la Unidad de Hemodialisis de la sucursal Vinces, año 2013 - Espinoza Escudero, Lisette Maryuri (2015)
This research project was conducted at the Committee of the Hemodialysis Unit of the Canton Vinces , Los Rios province , having a duration of 49 days, has 103 patients , provides free service to patients with renal failure have a building of a multipurpose plant and patients , and is sponsored by ministry of public health and complies with the laws. Management evaluation facilitated a quantitative and qualitative analysis and the budgetary impact. He was raised as a general objective to audit management and its impact on the budget in the Hemodialysis Unit of the Vinces canton 2013 and the specific objectives it is to establish the importance of the review of legislation governing the activities, as well as evaluate the system internal control, identify findings, the scrutiny of critical areas and finally write the report and communicate the results of the audit in the hemodialysis unit. Methods were used : inductive -deductive , analytic-synthetic and statistical ; the types of research literature and field were specifically because they held at the scene ; research techniques were used for making qualitative information through interviews , surveys , in the area of management, accounting and human talent , the results reflect a confidence level of risk, control of 27 % likewise with audit risk of 1.18 % in the accounting department a confidence level of 73% control risk of 27% and a risk of 0.59 % audit , human talent finally recorded a confidence level of 72 % , risk 28 % control and audit risk of 0.59 %.